Efisiensi Penggunaan Input Produksi Usaha Tani Padi (Studi Kasus pada Usaha Tani Padi Mitra PT. Wilmar Padi Indonesia di Kecamatan Paron Kabupaten Ngawi Provinsi Jawa Timur) - Marwanti, Marwanti; Ichdayati, Lilis Imamah; Nugraha, Achmad Tjachja (Universitas Galuh, 2025)
Input for rice farming that does not comply with the recommended dosage is inefficient because it causes farming productivity to not be optimal. This research is based on a partnership between farmers and PT. WPI in an effort to increase the productivity of rice farming to support the realization of food security. Based on the background of this problem, the aim of this research is to analyze (1) the characteristics of farmers (2) the use of production inputs for rice farming partners of PT. WPI, and independent farming businesses, (3) efficient use of production inputs from PT partner farming businesses. WPI, and independent. The method used is mixed method research with primary and secondary data. Respondents were determined using proportional random sampling. Conclusion of the research results: a) Judging from the aspects of age, education, experience, family size and main occupation, the characteristics of PT. WPI partner farmers are not significantly different from the characteristics of independent farmers. b) Input from partner and independent farming businesses, consisting of land, seeds, urea fertilizer, SP36, NPK, organic and the amount of labor has a significant effect on farming production. c) The use of production inputs in partner and independent farming businesses is not/is not yet efficient. Use of organic fertilizer in partner farming businesses of PT. WPI still needs to be added, MR > MC. Meanwhile, the volume of seeds, Urea fertilizer, SP36, NPK and labor usage does not have to be increased because MR < MC. The use of independent farming inputs has not yet reached optimal levels. To achieve an efficient level of input use, Urea, SP36, NPK, Organic fertilizer and labor are farming inputs whose volume of use must be increased. Input seeds whose usage rate does not have to be increased.